1970
DOI: 10.1017/s0022112070002677
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flow drag reduction and degradation with dilute polymer solutions

Abstract: Experimental studies of drag reduction and polymer degradation in turbulent pipe flow with dilute water solutions of unfractionated polyethylene oxide are described. Drag reduction results indicate that the magnitude of the reduction cannot be correlated on the basis of weight average molecular weight, rather the phenomenon depends strongly on the concentration of the highest molecular weight species present in the molecular weight distribution. Polymer degradation in turbulent flow is found to be severe for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 5 publications
3
60
0
Order By: Relevance
“…17,[22][23][24][25][26][27][28][29] The rate of shear degradation is greatest for high molecular weight polymers at low concentration. [27][28][29] Shear degradation typically results in a rapid decrease in molecular weight that approaches a limiting polymer molecular weight (M tϱ ) after long degradation times.…”
mentioning
confidence: 99%
“…17,[22][23][24][25][26][27][28][29] The rate of shear degradation is greatest for high molecular weight polymers at low concentration. [27][28][29] Shear degradation typically results in a rapid decrease in molecular weight that approaches a limiting polymer molecular weight (M tϱ ) after long degradation times.…”
mentioning
confidence: 99%
“…Until now, some researches [60,[64][65][66][67][68][69] have indicated that polymer molecular weight, molecular weight distribution, temperature, solvent solubility, polymer concentration, turbulent intensity, preparation and storage methods, entrance or end effects, and flow geometry may influence polymer degradation in turbulent flows. Nevertheless, it is noteworthy that due to various experimental conditions some conflicting results still exist when explaining degradation with the above factors.…”
Section: Effects Of Polymer Degradationmentioning
confidence: 99%
“…[I 17,124,125] an electrolyte Polyethylene oxide Hydrocarbons, [126,127] e. g. benzene trichloroethylene Polyethylene oxide Blood transfusion [128] fluids Polyacrylamide Water [103,108,109,119, [126] A study of the drag reducing ability of the above polymers has led to the conclusion that any macromolecular substance with a linear structure and high molecular weight, i. e. above 500,000, is a good drag reducer. The advantage of polymers is that they are effective at very low concentrations; but, as they are very prone to mechanical degradation in dilute solutions [157][158][159][160][161] they have limited practical applicability.…”
Section: Drag Reduction With Polymer Solutionsmentioning
confidence: 99%
“…But Paterson [157] found pipe drag reduction with poly(ethylene oxide) solutions as dilute as 0.03 ppm, and, at the molecular separation distances and volume fractions involved, it is quite unlikely that molecular entanglement could play any part in drag reduction. Nevertheless, Ellis et al [254] showed that polymer solutions stored for several weeks showed lower drag reduction than freshly mixed ones, the implication being that there has been a molecular disentanglement during storage.…”
mentioning
confidence: 99%